Oxysterols - new players in regulation of Natural Killer cells - Choi, Chloe Chi Shan (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2023)
Natural Killer (NK) cells are cytotoxic, innate lymphocytes that play a crucial role in mediating viral and tumour responses as well as supporting tissue homeostasis. Due to their fast acting immune response independent of antigen recognition against tumour cells, NK cells hold great potential for developing new treatments and cancer immunotherapies. Our knowledge of NK cell metabolism has evolved over the recent years and has highlighted the significant connection between metabolism and NK cell effector function. For instance, Sterol Regulatory Element Binding Proteins (SREBPs) were found to be crucial regulators of NK cell metabolic and effector function. SREBP is required for cytokine-mediated induction of NK cell metabolism supporting elevated rates of glycolysis and OxPhos. In NK cells, SREBP support elevated rates of glycolysis and OXPHOS by supporting the citrate malate shuttle, a non-canonical TCA cycle, through inducing the expression of Slc25a1 and ATP citrate lyase. Inhibition of SREBP or the citrate malate shuttle prevents elevated rates of NK cell metabolism and impairs the production of IFNγ and NK cell cytotoxicity. Oxysterols are oxygenated derivatives of cholesterol known for their conventional role in mediating cholesterol homeostasis. However, there is emerging evidence and ongoing studies revealing diverse immunoregulatory roles of oxysterols and the host immune response in multiple pathological settings. Indeed, in multiple diseases, but not limited to infection, cancer, autoimmunity and atherosclerosis, there are aberrant levels of oxysterols which contribute to immune dysregulation and dysfunction. This study aims to understand the immunoregulatory role of oxysterols for NK cell biology. Two oxysterols were focused upon in this study, 25-Hydroxycholesterol (25HC) and 27- Hydroxycholesterol (27HC). Both oxysterols can become elevated in certain immunological situations such as viral infection and cancer and have the potential to regulate NK cell responses. 25HC is generated by the interferon inducible gene, Ch25h and is expressed by macrophages during viral infection. 27HC is generated by the cytochrome p450 enzyme Cyp27a1 and is the most abundant oxysterol in the human serum. 27HC was identified as the first endogenous Selective Estrogen Receptor Modulator (SERM), known for its potency in ER+ breast cancer progression. Previously, v 27HC had only been shown to inhibit SREBP activity in hepatocytes. This study identified 27HC as a potent inhibitor of SREBP activation and as a result SREBP-controlled metabolism, glycolysis and OxPhos in NK cells. 27HC or 25HC exposure at any stage of NK cell activation, downregulate SREBP activity, as determined by reduced SREBP target genes expression. 27HC and 25HC exposure results in reduced rates of NK cell metabolism and loss of NK cell effector function, inhibition of IFNγ production and a near complete loss of NK cytotoxicity. The data show that irrespective of whether oxysterols were added during NK cell activation or after previous activation, the capacity of NK cell to kill tumour target tumour cells was significantly decreased. Overall, this study reveal that NK cells exposed to immunosuppressive oxysterols have severe metabolic defects resulting in significant loss in IFNγ production and cytotoxicity. This study also revealed that oxysterol exposure led to a significant decrease in amino acid uptake through Slc7a5. Previous studies argue that amino acid uptake into NK cells is important for NK cells as it supports cellular signalling transduction important for supporting metabolism and function. To examine the impact of impaired amino acid uptake into NK cells for antitumour functions a transgenic mouse was generated in which NK cells selectively lack the expression of Slc7a5. Loss of Slc7a5 in NK cells did not affect NK cell development and maturation nor initial activation. However, NK cells deficient of Slc7a5 activated in vivo fail to complete blastogenesis and fail to normally upregulate metabolic pathways. Consequently, these NK cells have impaired antitumour effector functions including the production of IFNγ and cytotoxicity against tumour cells. Indeed, mice containing Slc7a5-null NK cells show significantly increased tumour burden when challenged with B16 melanoma tumour cells. Taken together, my research has made important discoveries in (1) its study of oxysterols and their influence on NK cell metabolism and cytotoxicity and (2) the importance of Slc7a5-mediated amino acid uptake for antitumour NK cell responses. The increased understanding of cellular mechanisms of NK cell regulation as a direct result of this research will have important implications in developing new and improved NK cell based immunotherapies.
APPROVED